Intracoronary imaging reduces target vessel failure in primary percutaneous coronary intervention. (25th November 2020) - Ho, C; Yeung, Y.K; Leung, C; Lee, P.H; So, T.C; Chiang, M.C.S; Wong, M.H; Tsang, C.F; Chui, S.F; Chan, K.C; Wong, C.Y; Fu, C.L; et al.
Abstract: Background: Intracoronary imaging during percutaneous coronary intervention (PCI) allows better delineation of lesion characteristics and more accurate vessel sizing compared with angiogram alone. However, the benefit and safety of its use in primary percutaneous coronary intervention (PPCI) is uncertain. Purpose: To determine whether the use of intracoronary imaging with intravascular ultrasound (IVUS) or optical coherence tomography (OCT)/ optical frequency domain imaging (OFDI) in PPCI is associated with better outcome. Method: From Jan 2014 to Dec 2018, all patients with PPCI performed in our hospital were retrospectively studied. Baseline and procedural characteristics of angiographic-guided versus imaging-guided PCI were analyzed. Primary endpoint was target vessel failure, and procedural outcomes were contrast volume, number of stents implanted, mean stent length and diameter and use of post-dilatation. Safety outcomes were post-operative acute kidney injury (AKI), need for renal replacement therapy (RRT) and occurrence of no/slow reflow. Results: A total of 408 patients were included, of which 223 (54.7%) used IVUS (n=176 80.3%) or OCT/OFDI (n=44 19.7%) during the procedure. Baseline and procedural characteristics were similar between both groups except more patients had history of PCI (12.6% vs 4.3% p=0.004) and left-main/ bifurcation lesions (12.6% vs 2.7% p<0.001). Intra-coronary imaging was associated with less target vessel failure during a median follow up of 22 months (Hazard ratio (HR): 0.59; 95% Confidence interval (CI): 0.36–0.97; p=0.036). Patients who had intra-coronary imaging during PPCI received more post-dilatation (77.1% vs 55.1% p<0.001), had longer (53mm vs 42mm p<0.001) and more stents (2 vs 1.67 p=0.003) implanted but had more contrast injected (151.2ml vs 130.6ml p=0.002). There was no statistically significant difference in mean stent diameter (3.07mm vs 3.02mm p=0.53), occurrence of slow/now reflow (15.3% vs 18.4% p=0.409), incidence of AKI (7.2% vs 10.8% p=0.197) or need for RRT (3.1% vs 5.4% p=0.254) between both groups. Conclusion: Use of intra-vascular imaging during PPCI was associated with less target vessel failure, longer and more stents implanted and more frequent use of post-dilatation. Further prospective randomized controlled trial is suggested to confirm this benefit. Funding Acknowledgement: Type of funding source: None